A review of lessons learned to inform capacity-building for sustainable nature-based tourism development in the European Union funded ÊºSupport to the Wild Coast Spatial Development Initiative Pilot ProgrammeÊº - Wright, Brian Bradley (Rhodes University, Faculty of Education, Department of Education, 2006)
This case-study establishes the influences of power-knowledge relationships on capacity-building for sustainability in the European Union Funded 'Wild Coast Spatial Development Initiative Pilot Programme' (EU Programme). It aims to capture the lessons learned for capacitybuilding to support nature-based tourism initiatives on the Wild Coast. The EU Programme aimed to achieve economic and social development of previously disadvantaged communities through nature-based tourism enterprises, and to develop capacity of local authorities and communities to support environmental management. The study discusses common trends in thematic categories emerging from the research data, and contextualises research findings in a broader development landscape. This study indicates that power-knowledge relations were reflected in the EU Programme's development ideology by an exclusionary development approach, which lacked a participatory ethos. This exclusionary approach did not support an enabling environment for capacity-building. This development approach, guiding the programme conceptualization, design and implementation processes, resulted in a programme with unrealistic objectives, time-frames and resource allocations; a programme resisted by provincial and local government. The study provides a causal link between participation, programme relevance, programme ownership, commitment of stakeholders, effective management and capacity-building for sustainable programme implementation. The study argues that the underlying motivation for the exclusionary EU development ideology in the programme is driven by a risk management strategy. This approach allows the EU to hold power in the development process, whereas, an inclusionary participative development methodology would require a more in-depth negotiation with stakeholders, thereby requiring the EU to relinquish existing levels of power and control. This may increase the risk of an unexpected programme design outcome and associated exposure to financial risk. It may also have a significant financial effect on donor countries' consultancies and consultants currently driving the development industry. This study recommends an interactive-participative methodology for programme design and implementation, if an enabling environment for capacity-building is to be created. In addition, all programme stakeholders must share contractual accountability for programme outcomes. This requires a paradigm shift in the EU development ideology to an inclusionary methodology. However, this research suggests that the current EU development approach will not voluntarily change. I, therefore, argue that South Africa needs to develop a legislative framework that will guide donor-funded development programme methodology, to support an enabling environment for capacity-building.
Keywords: Wild Coast Spatial Development Initiative Pilot Programme; Sustainable development -- South Africa -- Eastern Cape -- Citizen participation; Sustainable development -- Environmental aspects -- South Africa -- Eastern Cape; Conservation and natural resources -- South Africa -- Eastern Cape; Natural resources -- Management -- South Africa -- Eastern Cape; Natural resources -- Management -- International cooperation; Rural development -- South Africa -- Eastern Cape; Eastern Cape (South Africa) -- Economic development; South Africa -- Foreign economic relations -- European Union countries; European Union countries -- Foreign economic relations -- South Africa; Ecotourism -- South Africa -- Eastern Cape -- Citizen participation; Tourism -- Environmental aspects -- South Africa -- Eastern Cape